The Acquisition of the NP in a German-Polish Bilingual Child. Evidence for Cross-Linguistic Influence - Anna Jachimek; Christine Dimroth; Klaus-Michael Köpcke (Discours)
This article contributes to a debate in the linguistic and psychological literature that centers around the question if grammatical systems which are acquired simultaneously are separate right from the beginning or if they overlap. We will have a close look on developmental patterns involved in the construction of reference systems in German and Polish by a bilingual child between age 1;5 to 4;0. The German and Polish reference system is of particular interest here because the languages are very different from each other in the relevant domain. We will show that there is cross-linguistic influence in bilingual acquisition and that the grammars are not strictly separated. Overgeneralization moves from German to Polish and not vice versa. We assume that the child prefers transparent form-function patterns and therefore temporarily favors the German system over the Polish one in the course of acquisition. In particular, the concept of definiteness turns out to be a driving force for the expansion of the noun phrase in both languages. Once acquired on the basis of the demonstrative pronoun das ‘this’ in German, demonstrative markers in definite contexts are then also attested in Polish. Thus, the demonstrative pronoun das can be considered as being the key to the system.